WORKING WITH HOMOSEXUAL CLIENTS: Application of Solution-Focused Therapy - Husmiati, Husmiati (Faculty of Psychology, Diponegoro University, 2012)
This article discusses the psychosocial problems dealt by gay, lesbian, and bisexual clients. Gay is an individual who has sex orientation to male, whereas lesbian is to female. Bisexual has both sex orientation towards male and female. This article also points out one approach called Solution-Focused Therapy (SFT) which can be applied in clinical practice. Working with SFT technique to homoerotic individual or group is significantly different to common people. Mental health experts such as social workers and clinical psychologists should have this understanding.Keywords: Homosexuality, client, clinical practice, therapy, solution focused